Stability and hydrogenation of polycyclic aromatic hydrocarbons during hydropyrolysis (HyPy) – Relevance for high maturity organic matter - Grotheer, Hendrik; Robert, Aileen; Greenwood, Paul; Grice, Kliti (Pergamon, 2015)
A series of hydropyrolysis (HyPy) experiments have been conducted on a small suite of authentic polycyclic aromatic hydrocarbons (PAHs: coronene, pyrene and perylene) to investigate the HyPy behaviour of these PAHs. This information may help in the interpretation of the structural significance of aromatic HyPy products, often detected in high abundance, from high maturity kerogens. The PAHs were separately treated by HyPy and were all susceptible to some extent of hydrogenation. Perylene also decomposed into low molecular weight aromatics (e.g. methylbiphenyls). Structurally, perylene is much less stable than the more condensed PAHs coronene and pyrene. The total product concentrations (wt% of starting PAH) from all experiments were consistently less than 100 wt%, probably due to either the condensation of semi-volatile products on walls of the transfer line prior to reaching the HyPy trap or the inefficient cold trapping of highly volatile products. Hydrogenation of PAHs was prevalent and was found to be significantly influenced by the addition of a Mo-S based catalyst and potentially the C/Mo ratio, but largely independent of the two final temperatures used (520 C and 550 C). The fully aromatised and hydrogenated products for any stable ring system may provide a general indication of the size distribution of aromatic units within the kerogen structure.